2007
DOI: 10.1038/sj.onc.1210260
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate alternative lengthening of telomeres genes by methionine restriction and RNA interference

Abstract: Telomerase-negative cancer cells can maintain their telomeres by a recombination-mediated alternative lengthening of telomeres (ALT) process. We reported previously that sequestration of MRE11/RAD50/NBS1 complexes represses ALT-mediated telomere length maintenance, and suppresses formation of ALT-associated promyelocytic leukemia (PML) bodies (APBs). APBs are PML bodies containing telomeric DNA and telomere-binding proteins, and are observed only in a small fraction of cells within asynchronously dividing ALT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
116
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 63 publications
8
116
3
Order By: Relevance
“…It has been shown that APBs are not always associated with the ALT phenotype (Fasching et al, 2005) and although candidate genes have been suggested (Jiang et al, 2007), no molecular markers for the detection of ALT have yet been confirmed. Previous work in cell line models highlighted an association of trimethyl K20 of histone H4 with both telomerase gene promoters in ALT cell lines, suggesting that chromatin modifications may have potential as novel markers of the ALT phenotype (Atkinson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that APBs are not always associated with the ALT phenotype (Fasching et al, 2005) and although candidate genes have been suggested (Jiang et al, 2007), no molecular markers for the detection of ALT have yet been confirmed. Previous work in cell line models highlighted an association of trimethyl K20 of histone H4 with both telomerase gene promoters in ALT cell lines, suggesting that chromatin modifications may have potential as novel markers of the ALT phenotype (Atkinson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed the requirement of PML, TRF1, TRF2, TIN2, RAP1 and the MRN complex proteins MRE11, RAD50 and NBS1 for APB formation in ALT cells. The close association of APB formation with ALT highlights these genes as candidate markers or regulators of the ALT pathway (Jiang et al, 2007); however, the mechanisms of regulation remain to be fully determined. We have recently shown that chromatin remodelling at the telomerase gene promoters is associated with a lack of expression of hTR and hTERT in some ALT cell lines, highlighting one potential mechanism for regulating the activation of ALT or telomerase (Atkinson et al, 2005).…”
mentioning
confidence: 99%
“…TRF2 and MUS81 interaction suggests that TRF2 may regulate MUS81 access to APBs, since TRF2 affects APBs formation in G 0 /G 1 cells. 15 To test this hypothesis, we examine the localization of MUS81 in APBs after depletion of TRF2. However, depletion of TRF2 does not change APB formation and localization of MUS81 to APBs at G 2 phase in ALT cells (data not shown), excluding that TRF2 regulates the sequences, sister chromatids can find sites of homology anywhere to align two telomere strands asymmetrically.…”
Section: Interaction Of Trf2 and Mus81 In The Alt Pathwaymentioning
confidence: 99%
“…14 A recent study reports that the proportion of ALT cells with APBs is increased following methionine starvation. 15 These induced APBs contain TRF1, TRF2, TIN2, RAP1, the PML protein, the MRN complex, 53BP1, SP100 and telomeric DNA. We have also observed induction of APBs containing telomeric DNA upon methionine restriction.…”
Section: Role Of Mus81 In Telomere Recombinationmentioning
confidence: 99%
See 1 more Smart Citation